2007
DOI: 10.1021/jp072974k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Aggregates in Aqueous Solutions of Bile Acid Salts. Molecular Dynamics Simulation Study

Abstract: The aggregation behavior of two bile acid salts (i.e., sodium cholate and sodium deoxycholate) has been studied in their aqueous solutions of three different concentrations (i.e., 30, 90,and 300 mM) by means of molecular dynamics computer simulations. To let the systems reach thermodynamic equilibrium, rather long simulations have been performed: the equilibration period, lasting for 20-50 ns, has been followed by a 20 ns long production phase, during which the average size of the bile aggregates (regarded to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 42 publications
(74 reference statements)
4
121
1
Order By: Relevance
“…Further, its applicability to nonplanar interfaces was shown for three systems previously simulated, namely, a quasi-spherical micelle of DPC, 55 several molecular models of soot, 58 and a secondary micellar aggregate of irregular shape composed of cholic acid molecules. 67 In addition, we proposed how to compute density profiles relative to intrinsic interfaces, irrespective of the latter being macroscopically planar or not, by using a simple Monte Carlo-based algorithm, which allows to estimate the volume of slabs at constant distance from the intrinsic surface, and normalize correctly the density histograms. This issue has been shown to be relevant not only in presence of complex interfaces, but also for macroscopically flat ones, because of the combined effect of capillary waves and of the finite width of fluid slabs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, its applicability to nonplanar interfaces was shown for three systems previously simulated, namely, a quasi-spherical micelle of DPC, 55 several molecular models of soot, 58 and a secondary micellar aggregate of irregular shape composed of cholic acid molecules. 67 In addition, we proposed how to compute density profiles relative to intrinsic interfaces, irrespective of the latter being macroscopically planar or not, by using a simple Monte Carlo-based algorithm, which allows to estimate the volume of slabs at constant distance from the intrinsic surface, and normalize correctly the density histograms. This issue has been shown to be relevant not only in presence of complex interfaces, but also for macroscopically flat ones, because of the combined effect of capillary waves and of the finite width of fluid slabs.…”
Section: Discussionmentioning
confidence: 99%
“…At relatively low concentrations they form regular micelles with an aggregation number of 2-10, while above a second critical micellar concentration these primary micelles form larger secondary aggregates by establishing hydrogen bonds between the hydrophilic surface groups of the primary micelles. 66,67 These secondary micelles are of rather irregular shape, 67,68 which makes them an excellent test system for our purposes.…”
Section: Secondary Cholic Acid Micellementioning
confidence: 99%
See 1 more Smart Citation
“…Although they are comparable to common surfactants, the general conclusion is that biosurfactants self-assemble in a different way than the standard surfactants. [1][2][3][4][5][6][7][8][9][10][11][12][13] Poly(ethyleneimine) (PEI) is a member of a large family of water-soluble polyamines having different molecular weights (M w ) and polymer architectures. Polyamines are weak bases and exhibit a cationic character depending on the degree of protonation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is not sufficient experimental evidence to corroborate this correlation. On the other hand, computer simulations by Pártay et al suggested that hydrogen bonding and hydrophobic interactions are important in the composition of primary micelles 10,11 . The molecular dynamics simulations also supported the theory that changes in the aggregate structure primary-secondary micelle contribute to micelle growth.…”
Section: Micelle Model Determined From T 1 Measurementmentioning
confidence: 99%